Analysis and evaluation of the leakage failure for clutch sleeve and shell. (June 2018) - Kan, Fuchao; Liu, Xintian; Xin, Xiufeng; Xu, Jiejie; Huang, Hu; Wang, Yansong
Abstract: To solve leakage failure of the product caused by uncertain factors, the clutch sleeve and shell are taken as an example for development of processing. Finite element model of clutch sleeve and shell is established, and the stress deformation is ascertained and analyzed under working load. Based on actual operating conditions of the clutch sleeve and shell, the mathematical model of leakage failure is established considering the factors of load, temperature, manufacturing error and assembling deviation. The clearance between the clutch sleeve and shell is determined and discussed using the model based on the influence of various factors. To reduce the size of the clearance, a relevant improvement that the increased step is added on outside of the sleeve is put forward. The results of discussion on the improved assembly and analysis of actual samples prove that the scheme is effective. Highlights: An improvement to reduce the clearance between the clutch sleeve and shell is proposed. A new multifactor influenced mathematical modeling is proposed in the analysis of leakage failure. The calculation results of the mathematical model are more accurate than the ordinary single-factor method.